2019
DOI: 10.1186/s12911-019-0915-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic medical record-based model to predict the risk of 90-day readmission for patients with heart failure

Abstract: Background Several heart failure (HF) risk models exist, however, most of them perform poorly when applied to real-world situations. This study aimed to develop a convenient and efficient risk model to identify patients with high readmission risk within 90 days of HF. Methods A multivariate logistic regression model was used to predict the risk of 90-day readmission. Data were extracted from electronic medical records from January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 35 publications
0
30
1
Order By: Relevance
“…A previous EVEREST analysis provided a comprehensive description of various factors in the course of HF patients who experience 90‐day all‐cause rehospitalization or death after discharge. 12 In addition, another moderately predictive model (AUC 0.730) looking at 90‐day all‐cause readmission identified the Charleston comorbidity index, NT pro‐BNP, and certain hematologic parameters as predictors in a Chinese cohort of HF patients after discharge 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous EVEREST analysis provided a comprehensive description of various factors in the course of HF patients who experience 90‐day all‐cause rehospitalization or death after discharge. 12 In addition, another moderately predictive model (AUC 0.730) looking at 90‐day all‐cause readmission identified the Charleston comorbidity index, NT pro‐BNP, and certain hematologic parameters as predictors in a Chinese cohort of HF patients after discharge 13 …”
Section: Discussionmentioning
confidence: 99%
“…However, window of vulnerability is likely longer, with the spike in event rates occurring out 90 days post‐discharge and plateauing thereafter 5,7 . Few existing HF risk prediction algorithms have explored readmission and death assessed over the post‐discharge phase transition out to 90 days 12‐14 …”
Section: Introductionmentioning
confidence: 99%
“…Among all diagnosis-specific studies, half of them (50%) built models to predict readmission among patients with heart-specific conditions. Among the 18 studies focused on heart conditions, 13 papers predicted readmissions among the HF population [ 56 60 , 63 , 65 71 ], 2 worked on AMI cohorts [ 61 , 62 ], 2 developed models on general cardiovascular disease patients [ 55 , 72 ], and 1 worked on the stroke population [ 64 ]. As shown in Fig.…”
Section: Application To Readmissionmentioning
confidence: 99%
“…Even with the emergence of the ML algorithm, 29 out of 36 articles adopted traditional statistical methods. Among these studies, ~ 90% used LR either as a baseline [ 56 , 58 , 60 , 62 64 , 68 , 73 , 74 , 76 78 , 83 , 85 87 ] or the main model in prediction [ 60 , 69 , 71 , 82 , 88 90 ], and 3 studies derived their own risk scores on the basis of LR variable coefficients [ 61 , 66 , 84 ]. In the remaining 3 papers, the prognosis of readmission was carried out with Cox regression survival analysis.…”
Section: Application To Readmissionmentioning
confidence: 99%
“…However, Cotter et al [ 7 ] concluded that the LACE index performed poorly in predicting 30-day readmission with the area under the receiver operating characteristic curve (AUC) of 0.55, while that of the logistic regression (LR) model was 0.57. Regression analysis method is a process of estimating the probability of target variables given some linear combination of the predictors, and has been widely applied to predict the readmission risk [ 8 , 9 ]. However, it is difficult to solve the nonlinear problem or multicollinearity among risk factors based on detailed clinical data.…”
Section: Introductionmentioning
confidence: 99%